Open innovation and innovative performance of Pakistani SMEs: Moderated mediation of knowledge management capability and innovative climate - Masood Ul Hassan; Asghar Iqbal (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
Drawing upon the organizational capabilities of knowledge management, the current study aims to examine the mediating role of knowledge management capability between open innovation and firm-level technological, structural, and entrepreneurial capabilities and the moderation role of innovation climate between open innovation and firm innovative performance. A questionnaire-based survey with a sample of 332 top managers of Pakistani SMEs across the service and manufacturing sectors was conducted. The study adopted partial least squares structural equation modeling (PLSSEM) to estimate moderated mediation using the SmartPLS 3.0. The results revealed that the organization structure contributes significantly, followed by ICTs and entrepreneurial orientation on SMEs' knowledge management capability. Mainly, the most robust knowledge management capability positively affects open innovation and mediates most significantly between open innovation and organization structure, followed by ICTs and entrepreneurial orientation. Finally, open innovation directly and through the moderation of innovative climate significantly impact SMEs' innovative performance. The findings suggest that improving the knowledge management capability and innovative climate means the mechanisms of mediation and moderation through which entrepreneurial orientation, ICTs, and organization structure impact the open innovation, which, in turn, impact SMEs' innovative performance. For policymakers, an important message is that SMEs do not innovate individually but with customers, competitors, suppliers, and others. The usefulness resides in advancing a comprehensive process of knowledge management capability and innovative climate, suggesting the mechanisms to transmit the effects of entrepreneurial orientation, ICTs, and organization structure to open innovation, thereby to SME's innovative performance.
Keywords: 330; knowledge management capability; open innovation; innovative performance; small and medium enterprises; information and communication technologies; organization structure